Analisis Penerapan Sistem Informasi Akuntansi Dalam Meningkatkan Efisiensi Pelaporan Keuangan Pada PT. Kimci Jaya Bersaudara - Gilbert Sabanari; Florance Moroki; Ananta Pratiwi (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to analyze the application of the Accounting Information System (SIA) in improving the efficiency of financial reporting at PT. Kimci Jaya Brothers. The background of this research focuses on financial reporting problems that were previously carried out manually, resulting in frequent delays, inaccuracies, and a high risk of human error. Therefore, the company implemented SIA to support more effective and efficient financial reporting processes. This research uses a qualitative method with a descriptive approach through observation, interview, and documentation techniques. The informants in this study consisted of managers and financial staff who were directly involved in the use of SIA and financial reporting activities. The results of the study show that the implementation of SIA is able to significantly improve the efficiency of financial reporting. This is characterized by improved system quality, information quality, and ease of use, which contribute to better reporting timeliness, higher data accuracy, and increased user satisfaction. Overall, the implementation of SIA has been proven to provide real benefits for companies in improving financial reporting efficiency and supporting more accurate, timely, and reliable managerial decision-making processes.